The role of age in treatment‐related adverse events in patients with head and neck cancer: A systematic review. Issue 7 (9th February 2019) - Coca‐Pelaz, Andrés; Halmos, Gyorgy B.; Strojan, Primož; de Bree, Remco; Bossi, Paolo; Bradford, Carol R.; Rinaldo, Alessandra; Vander Poorten, Vincent; Sanabria, Alvaro; Takes, Robert P.; Ferlito, Alfio
Abstract: Head and neck squamous cell carcinoma (HNSCC) is often diagnosed in advanced stage and therefore requires aggressive, multimodal treatment. Elderly patients are often excluded from standard therapy regimens purely based on age. This clinical review aims to collect all published data in the literature on treatment modality selection in elderly patients and on age‐related adverse events following treatment of HNSCC. We performed a literature search for articles on the treatment of HNSCC in elderly patients. Most of the articles were retrospective studies with the consequent limitations. It can be concluded that age is not an absolute contraindication for intensive treatment and comorbidity is an important predictor of outcome, but not the only one. Despite the existence of multiple tools for pretreatment evaluation, there are not consistent data on their use.